Enhancing CSR activities to increase bank attractiveness - Tang My Sang; Nguyen Tien Hung; Nguyen Ngoc Dinh (Cogent Business & Management, 2023)
This study is carried out to investigate the impact of CSR activities on bank attractiveness in Vietnamese commercial banks. The data was collected from 1167 customers in Ho Chi Minh city. The independent variables were CSR for customers, CSR for employees, and CSR for social public welfare, while the dependent variable was bank attractiveness, and an intermediate variable was bank reputation. SmartPLS 3.0 software was used to process the model in two steps. The findings revealed that all three components of CSR had a direct effect on bank reputation, with CSR for social public welfare having the greatest influence. Bank attractiveness also had a significant impact on a bank's reputation. CSR components all had an indirect impact on bank attractiveness via the mediated influence of reputation. Academically, the research findings indicate that CSR activities are now important in attracting customers for Vietnamese commercial banks. In practice, the findings assist bank administrators in recognizing the importance of factors in CSR activities and being proactive in implementing and formulating strategies.
Keywords: 650; attractiveness; bank; CSR; reputation; sustainable development